Respuesta :
Distribute 4.5 to 8- x and distribute -2.5 to 3x-24 to get 36-4.5x+36+102-7.5x+60, then add like terms to get 3x=90
Simplifying
4.5(8 + -1x) + 36 = 102 + -2.5(3x + 24)
(8 * 4.5 + -1x * 4.5) + 36 = 102 + -2.5(3x + 24)
(36 + -4.5x) + 36 = 102 + -2.5(3x + 24)
Reorder the terms:
36 + 36 + -4.5x = 102 + -2.5(3x + 24)
Combine like terms: 36 + 36 = 72 72 + -4.5x = 102 + -2.5(3x + 24)
Reorder the terms: 72 + -4.5x = 102 + -2.5(24 + 3x) 72 + -4.5x = 102 + (24 * -2.5 + 3x * -2.5) 72 + -4.5x = 102 + (-60 + -7.5x)
Combine like terms: 102 + -60 = 42 72 + -4.5x = 42 + -7.5x Solving 72 + -4.5x = 42 + -7.5x Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '7.5x' to each side of the equation. 72 + -4.5x + 7.5x = 42 + -7.5x + 7.5x
Combine like terms: -4.5x + 7.5x = 3x 72 + 3x = 42 + -7.5x + 7.5x
Combine like terms: -7.5x + 7.5x = 0.0 72 + 3x = 42 + 0.0 72 + 3x = 42
Add '-72' to each side of the equation. 72 + -72 + 3x = 42 + -72
Combine like terms: 72 + -72 = 0 0 + 3x = 42 + -72 3x = 42 + -72
Combine like terms: 42 + -72 = -30 3x = -30
Divide each side by '3'. x = -10
Simplifying x = -10
Combine like terms: 36 + 36 = 72 72 + -4.5x = 102 + -2.5(3x + 24)
Reorder the terms: 72 + -4.5x = 102 + -2.5(24 + 3x) 72 + -4.5x = 102 + (24 * -2.5 + 3x * -2.5) 72 + -4.5x = 102 + (-60 + -7.5x)
Combine like terms: 102 + -60 = 42 72 + -4.5x = 42 + -7.5x Solving 72 + -4.5x = 42 + -7.5x Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '7.5x' to each side of the equation. 72 + -4.5x + 7.5x = 42 + -7.5x + 7.5x
Combine like terms: -4.5x + 7.5x = 3x 72 + 3x = 42 + -7.5x + 7.5x
Combine like terms: -7.5x + 7.5x = 0.0 72 + 3x = 42 + 0.0 72 + 3x = 42
Add '-72' to each side of the equation. 72 + -72 + 3x = 42 + -72
Combine like terms: 72 + -72 = 0 0 + 3x = 42 + -72 3x = 42 + -72
Combine like terms: 42 + -72 = -30 3x = -30
Divide each side by '3'. x = -10
Simplifying x = -10